Opportunity Amid Crisis in Medical Education: Teaching During the Pandemic of COVID-19 - Rahayu, Gandes Retno (Dove Medical Press Ltd, 2022)
Purpose: The pandemic of COVID-19 had reinforced adaptations in medical education. It was challenging, especially for developing countries where resources were scarce. This study examined the implementation of teaching and learning adaptation during the pandemic in a low-resource country as perceived by teachers. We also present the opportunities that arise from the adaptation process. Participants and Methods: The participants of this study (n=24) were teachers in an undergraduate medical program. This study employed a qualitative approach using focus group discussions (FGDs) to collect the teachers’ perceptions. Thematic analysis was performed to analyse the data. Results: Teachers’ perceptions were categorized into 19 subthemes and were accentuated into four general themes; learning facilitation, assessment during the pandemic, learning resources, and competence achievement. We discovered both challenges as well as opportunities in each theme due to the shifting of learning from offline to online learning. Flexibility and innovation were regarded as the most important opportunities and were perceived to hold potential for medical education in the future. Knowledge acquisition was most benefited from this adaptation. Facilitating skill acquisition and burnout were the major challenges. Conclusion: Despite the challenges, including burnout, skills acquisition, and risk in academic integrity, innovations in medical education were strengthened during the pandemic of COVID-19. They also provided a positive influence regarding achievement in the cognitive aspect. Faculty development programs need to be encouraged to improve teachers’ capacity in the future. © 2022 Rahayu et al.